The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41386-020-0662-7
|View full text |Cite
|
Sign up to set email alerts
|

Extra-striatal D2/3 receptor availability in youth at risk for addiction

Abstract: The neurobiological traits that confer risk for addictions remain poorly understood. However, dopaminergic function throughout the prefrontal cortex, limbic system, and upper brainstem has been implicated in behavioral features that influence addiction vulnerability, including poor impulse control, and altered sensitivity to rewards and punishments (i.e., externalizing features). To test these associations in humans, we measured type-2/3 dopamine receptor (DA 2/3 R) availability in youth at high vs. low risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…Whereas in the direct group comparison, there was no significant difference between the BP of LR and AUD subjects as well as LR and HR subjects, dopamine D2/3 availability was altered in the rACC and vlPFC of HR compared to AUD subjects. This finding is in line with the work of Jaworska et al [21] which observed higher levels of extrastriatal postsynaptic D2/3 receptors in adolescents at HR for developing an addiction. Further, Pfeifer et al [51] observed higher extrastriatal BP to be correlated with the subjective effect of liking alcohol after an acute intravenously applied alcohol infusion revealing a potential clinical link.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas in the direct group comparison, there was no significant difference between the BP of LR and AUD subjects as well as LR and HR subjects, dopamine D2/3 availability was altered in the rACC and vlPFC of HR compared to AUD subjects. This finding is in line with the work of Jaworska et al [21] which observed higher levels of extrastriatal postsynaptic D2/3 receptors in adolescents at HR for developing an addiction. Further, Pfeifer et al [51] observed higher extrastriatal BP to be correlated with the subjective effect of liking alcohol after an acute intravenously applied alcohol infusion revealing a potential clinical link.…”
Section: Discussionsupporting
confidence: 93%
“…OFC volume and connectivity, and amygdala connectivity are associated with substance use, SUD and subclinical anxiety and depression measures; however, these brain measures have yet to be informative in clinical diagnoses [73,82,96,122]. Interestingly, studies indicated that blunted striatal activity was associated with depressive symptoms, but not substance use or SUD [57,97], in contrast to our original hypothesis [60]. These neural findings are highly congruent with the epidemiological literature: Externalizing disorders have been more consistently linked with SUD than internalizing disorders [44].…”
Section: Discussioncontrasting
confidence: 65%
“…Abnormalities in the structure, function, and chemistry of differentiable neural pathways are suggested to underlie the increased risk of SUD within each class of psychopathology. While adolescents with externalizing symptoms at risk of SUD demonstrate weaker prefrontal activity and cortical thinning, their counterparts with internalizing symptoms show blunted striatal activity [52,60]. This suggests unique neural pathways to SUD in each class of psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…We show the comparisons between tracers in Fig. S2b for the following neurotransmitter receptors/transporters: 5-HT1 A [12,105], 5-HT1 B [12,39,105], 5-HT2 A [12,105,124], 5-HTT [12,105], CB 1 [64,79], D 2 [2,55,101,117], DAT [29,104], GABA A [29,78], MOR [57,126], and NET [27,48]. Here we make some specific notes: (1) 5-HTT and GABA A involve comparisons between the same tracers (DASB and flumazenil, respectively) but one map is autoradiography-informed (see [12] and [78]) and the other is not [29,30,105]; (2) raclopride is a popular D 2 tracer but has unreliable binding in the cortex, and is therefore an inappropriate tracer to use for mapping D 2 densities in the cortex, but we show its comparison to FLB457 and another D 2 tracer, fallypride, for completeness [2,22,55]; (3) the chosen carfentanil (MOR) map was collated across carfentanil images in the PET Turku Centre database-since our alternative map is a partly overlapping subset of participants, we did not combine the tracers into a single mean map [57,126].…”
Section: Pet Data Acquisitionmentioning
confidence: 99%